Aplikasi Mobile Berbasis Android untuk Media Promosi Shirouoshien - akhsanitaqwiym; Lisa Amelia (Teknomatika, 2020)
Promotion is an activity carried out by business owners in an effort to introduce and offer products and services offered to prospective buyers. Promotion can be carried out traditionally and digitally. Providing information and disseminating information on the promotion of a product or service is a necessity in an effort to expand the prey of the business market. The purpose of designing and building an Android-based Shirouoshien promotion application system is as one of the information media solutions that can be easily found in digital searches. The research method used by the waterfall method starts from data collection, system design, code generation, testing, and implementation. The conclusion of making this application is an android application can provide convenience in finding information digitally and one of the media that facilitates efforts to promote products and services offered by Shirouoshien.